ANALISIS KINERJA PEMASARAN PADA INDUSTRI OLAHAN MAKANAN DI KABUPATEN KOLAKA - Hasbiadi Hasbiadi; Puryantoro Puryantoro; La Mpia; Juniaty Arruan Bulawan (Jurnal Ekonomi Integra, 2021)
The food processing industry is currently growing rapidly in Kolaka Regency, marketing focuses on local travelers and tourists. The marketing pattern has been carried out online, but during the Covid-19 Pandemic it caused decrease the purchasing power and travelers. To maintain sales turnover, the industry must know the factors that affect marketing performance. Research purposes are to analyze the effect of product innovation on the marketing performance and to analyze the effect of marketing strategy creativity on the marketing performance of the food processing industry in Kolaka Regency. The research design is a survey research. The sampling technique is the census or saturated sampling technique where the research sample is all members of the population (51 Industries). The analytical technique used is multiple linear regression analysis and t test. The research results are product innovation variables have a positive and significant effect on the marketing performance with variable indicators including product expansion, product imitation, and new products. The marketing strategy creativity variable has a positive and significant effect on the marketing performance with variable indicators including individual characteristics, creative processes, and work environment